Acid rain induced leakage of Ca, Mg, Zn, Fe from plant photosynthetic organs – Testing for deciduous and dicotyledons. (February 2021) - Diatta, Jean; Youssef, Naglaa; Tylman, Oskar; Grzebisz, Witold; Markert, Bernd; Drobek, Leszek; Wünschmann, Simone; Bebek, Małgorzata; Mitko, Krzysztof; Lejwoda, Paweł
Highlights: Acid rains exert less deleterious effects to dicotyledonous than deciduous plants. Leakage of minerals as power function (deciduous), and linearly (dicotyledons). High Ca, Mg levels in deciduous leaves is efficient buffer inactivating acid rain. Mineral photosynthetic index discriminates vulnerable and resistant plant species. Reserve and bio-active Ca, Mg, Zn, Fe concentrations as phyto-fence to acid rains. Abstract: Simulated acid rains (AR), (pH 3.0, 3.5, 4.0, 4.5, 5.0, 5.5) were applied to green leaves of 13 deciduous trees (DT) and 10 species of dicotyledonous plants (DP). All were incubated at 23 °C within a growth chamber for 72 h. After the contact time, the leachates were analyzfor pH and next mineral elements: Ca, Mg, Fe, Zn. Total leaf concentrations of Ca and Mg have exhibited different relationships with Mg(DT)  = 6.85Ca(DT) 0.566, R 2  = 0.64 and Mg(DP)  = 0.079Ca(DP)  + 318.8, R 2  = 0.41. Leakage process revealed that intra-species variation for DT follows: Mg (107.3%) > Ca (106.0%) > Zn (90.3%) > Fe (59.8%), implying that the leaking effect was much more pronounced for alkaline elements (Ca, Mg). Dicotyledonous plants (DP), displayed a similar pattern but less varied: Mg (78.7%) > Ca (75.6%) > Zn (66.5%) > Fe (55.8%). The elaborated mineral photosynthetic index (MPI), [Mg/(Zn + Fe)] revealed that 77% of deciduous species represented very low to intermediate photosynthetic recovery, meaning that highly acid rain impacted trees will be surviving less or none. High DT survivors should be maple, linden and hornbeam. Dicotyledonous plants (DP) covered 70% of high to very high survival feature, where cucumber, cabbage and daisy prevailed. We stipulate that regreening of zones endangered by acid rains or planning green urban spaces should consider tree species with much more higher Ca concentrations in leaves. Both Ca 2+ and Mg 2+ intracellular hydrolysis appears as an efficient buffer inactivating acidity.